Terapi Kognitif Perilaku Religius untuk Menurunkan Kecemasan terhadap Kematian pada Penderita HIV/AIDS - Irawati, Deasy; Subandi, M.A.; Kumolohadi, Retno (Fakultas Psikologi dan Ilmu Sosial Budaya, Universitas Islam Indonesia, 2011)
This study was aimed to understand the effect of giving religious cognitive therapy in reducing anziety of death in people with HIV/AIDS. There are 8 woman with HIV/AIDS as subject. The data was collected using a scale of anxiety about death, interviews, and observation. The design of the study is a pre test-post test Control Group Design. Analysis of the study is quantitative and qualitative analysis. The research used Mann-Whitney test analysis to determine whether there is influence of cognitive behavioral therapy in reducing anxiety to wards religiously death of people with HIV/AIDS in the study group before and after being given the training provided the training. Qualitative analysis are based on observations, interviews, and worksheets. The results of the pre-test and post-test anxiety on mortality suggests that there are differences in anxiety about the death after being given training by the value Z=-2.309, p=0.021, p<0.05. In the post test and follow-up of research groups there are differences in anxiety about death with a value of Z=-2.323, p=0.020, p<0.05. The conclusion of this study is that there are differences in levels of anxiety towards death on the subject after the follow-up study.